Outcome of neonates receiving high frequency oscillation ventilation in a tertiary care institution - M. S., Kalpana; S., Kalyani (International Journal of Contemporary Pediatrics, 2019)
Background: High-frequency ventilation is defined as ventilation at a frequency greater than four times normal respiratory rate. HFOV has been used as alternative to conventional ventilation and in respiratory failure of various etiologies. The aim of the study was to identify the indications of neonates receiving HFOV, following failure of conventional ventilation. Methods: Total 93 neonates were enrolled in the study who received HFOV. The criteria for starting HFOV, the ventilator settings, CBG and ABG analysis, oxygenation index (OI), duration of ventilation and complications of ventilation were recorded during CMV and subsequently when shifted over to HFOV. Outcomes such as oxygenation, lung recruitment and ventilation and survival were monitored. Results: Total 66 neonates (71%) were term babies. Among the 27 preterm 18 (18.4%) were 33-34±6 weeks of gestational age. Male were 50 in number (53.8%) and female were 43 (46.2%). The male: female ratio was 50:43. Disease specific survival analysis revealed more than 50% survival in cases of pneumonia, collapse, air leak, MAS and pulmonary hemorrhage. 16 out of 33 babies (48.5%) with PPHN survived. All 3 babies with CDH expired. Of the 93 neonates included in the study, 53 (57%) of them were discharged home. The major complications noted while on HFOV were- 38 neonates (40.8%) had air leaks. Instead of, ventilator associated pneumonia was present in 42 of them (45.1%) and none of them developed IVH or NTB (Necrotising tracheo bronchitis). Conclusions: HFOV is a safe and effective technique in the treatment of neonates with respiratory failure in whom CMV fails. The results of present study show that rescue HFOV improved oxygenation, ventilation and lung recruitment and there was no increased incidence of IVH.